Debilitamiento biopolítico: afrocolombianos en Manos sucias (2014). Issue 1 (2nd January 2020) - Rocha, Carolina
ABSTRACT: In this essay, I rely on Jasbir Puar's concept of debility to analyze the American-Colombian co-production Manos sucias (Joseph Wladyka 2014), a film that has garnered recognition both in Colombia and abroad for its nuanced representation of Afrodescendants. The film depicts two Afrocolombian brothers, Delio and Jacobo, who live in the Pacific coast of Colombia, an area that has a high concentration of Afrodescendants. Despite the constitutional change of 1991 to recognize their rights to their culture, traditions, and lands, Afrocolombians are portrayed as experiencing debility due to the invasion of narcotraffickers, guerrilla groups, and paramilitary, all of whom disrupt their way of life, and even force them into modern forms of slavery. Central to my argument is who has the right to see or who is seen. Manos sucias also revolves around the moral dilemma faced by the young characters of learning to use violence as a way to survive in the dangerous trade of drug trafficking.